Strategi Penetrasi Harga Untuk Mengoptimalkan Penjualan Produk Hijab Syar’i Pada Toko Addini Hijab di Kota Bukittinggi - Vadila Laok Oktavia; Rini Elvira (SYNERGY: Jurnal Bisnis dan Manajemen, 2026)
This research has the problem of decreasing sales of new products, which aims to find out the price penetration strategy for Bella Syar'i Hijab products at the Addini Hijab Toko Pasar Aur Bukitinggi, with this research emphasizing the penetration strategy as an effort to optimize sales while remaining based on sharia business principles, namely honesty, justice, responsibility, and the implementation of buying and selling based on divine values. The Addini Hijab shop is located in Pasar Aur, Bukittinggi City, West Sumatra Province. The type of research used is Quantitative Descriptive and Survey research, namely data collected directly by the author through distributing closed questionnaires, interviews with the owners and employees of the Addini Shop. The data analysis used is SWOT analysis, namely analysis of the data obtained to identify strengths, weaknesses, opportunities and threats. The research results show that the Addini Hijab Store is in the SO Strategy with the highest score of 6.86, which indicates strong internal conditions and large market opportunities. The main strength lies in the affordable price of the hijab, in accordance with consumers' purchasing ability, proportional to the benefits of the product, and high customer loyalty. Dominant opportunities include market growth, good business prospects, and competitive product advantages. However, price competition and the emergence of similar products at lower prices need to be anticipated through strengthening product value and consistently applying sharia marketing principles